South as a Sight â€˜å—æ–¹â€™, from a branch to a necessity to World Literature - Zhao, Yixuan (Journal of Research in Social Science and Humanities, 2023)
In the discussion and debates on the world literature system, methodologies and methods is a topic that is valued. Moretti and Apter have prominent different opinions on the adoption of digital or abstract data outside texts and contexts. The way Moretti views the world literature system is highly based on historiography and studies of the Annual School’s influence and Immanuel Wallerstein’s World System, so the western-centric academic genes were inherited to some degree. However, the world system inspired Chinese Characters writing worlds and help form Sinophone Literature, which gives a possible response to Apter’s questioning. Among the system, ‘South’ or South Sight is a different way to deal with intercultural contexts. The article attempts to explain where the dialogue may happen and its reason from other academic traditions. Furthermore, try to methodize the South Sight as a supplement to the world literature approach.